Butelase 1 : the fastest known ligase for protein cyclization and ligation - Chen, Shu Bee (2014)
Peptide cyclization confers increased conformational stability and rigidity against metabolic and thermal denaturation. Encouraged by potential usage of cyclic peptides in the therapeutic applications, methods of protein cyclization and ligation have been developed such as native chemical ligation, intein-, PatG- and sortase A- mediated transpeptidase activity. However, with various kinds of limitations in restricting the practical applications, a natural occurring ligase, butelase 1 has been discovered and isolated from Clitoria ternatea recently. Here, I perform the enzyme kinetics characterization of butelase 1 for cyclization of various peptides of plant and animal origin and explore the potential applications in mediating intermolecular ligation. With the kcat value up to 4 s-1 and the catalytic efficiency of 71,384 M-1s-1, butelase 1 is the fastest known ligase. Butelase 1, an Asn-specific ligase, cyclizes various bioactive peptides quantitatively in a head-to-tail manner with conversion yield >95% and displays broad substrate specificity. Moreover, it is useful for introducing a functional group such as biotin and fluorophore to proteins by using GFP, monoclonal antibody and darpin as model proteins. The results show that butelase 1 would play an important role in the future bioengineering and pharmaceutical applications.